IPTEKS SISTEM INFORMASI AKUNTANSI DALAM AKTIVITAS PENCAIRAN DANA PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Mile, Abdul Wahid Supriatna; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
The system is a series of two or more interconnected components, which is interact to achieve a goal. This study aims to determine the role of accounting information systems in disbursing funds in the Regional Office of the Ministry of Religion of North Sulawesi Province. The method used in this writing is qualitative descriptive. The results of this study can be seen that the importance of accounting information systems for the Regional Office of the Ministry of Religion of North Sulawesi Province. With the existence of a good Accounting Information System, companies can carry out operations and information processes more effectively and efficiently because of the controls that control these processes so that the results achieved can be in accordance with the objectives of the agency.Keyword: Accounting information system, procedure for disbursing funds